Test of electrical resistivity and current diffusion modelling on MAST and JET. (16th November 2017) - Keeling, D.L.; Challis, C.D.; Jenkins, I.; Hawkes, N.C.; Lupelli, I.; Michael, C.; de Bock, M.F.M.
Abstract: Experiments have been carried out on the MAST and JET tokamaks intended to compare the electrical resistivity of the plasma with theoretical formulations. The tests consist of obtaining motional stark effect (MSE) measurements in MHD-free plasmas during plasma current ramp-up (JET and MAST), ramp-down (MAST) and in stationary state (JET and MAST). Simulations of these plasmas are then performed in which the current profile evolution is calculated according to the poloidal field diffusion equation (PFDE) with classical or neoclassical resistivity. Synthetic MSE data are produced in the simulations for direct comparison with the experimental data. It is found that the toroidal current profile evolution modelled using neoclassical resistivity did not match the experimental observations on either device during current ramp-up or ramp-down as concluded from comparison of experimental and synthetic MSE profiles. In these phases, use of neoclassical resistivity in the modelling systematically overestimates the rate of current profile evolution. During the stationary state however, the modelled toroidal current profile matched experimental observations to a high degree of accuracy on both devices using neoclassical resistivity. Whilst no solution to the mismatch in the dynamic phases of the plasma is proposed, it is suggested that some physical process other than MHD which is not captured by the simple diffusive model of current profile evolution is responsible.